MENINGKATKAN HASIL BELAJAR IPA TERINTEGRASI AL-QURAN MATERI POTENSI MANUSIA PADA KELAS IV SD MENGGUNAKAN MEDIA VIDEO ANIMASI - Qolbiyah, Aini; Hitami, Munzir; Yusuf, Kadar M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this research is to find out the increase in science learning outcomes integrated with the Qur'an in the material on Human Potential in class IV SD with learning animation video media. This research is a development research using the ADDIE model. This study produced an animated science learning video to improve science learning outcomes in grade IV elementary school which has been tested for proper validity. The results showed that the teacher obtained a "very good" qualification result of 4.50 in using animated learning video media with integrated Al-Qur'an science content.